Recent Rebounding of the Post‐Landfall Hurricane Wind Decay Period Over the Continental United States - Yi‐Jie Zhu; Jennifer M. Collins (Geophysical Research Letters)
Abstract The hurricane post‐landfall wind speed decay is closely linked to the inland damage potential. We introduce the wind decay period as a new metric for assessing the time required for a landfalling hurricane to dissipate to the intensity below tropical storm strength. In the continental United States, the wind decay period was generally decreasing during 1900–1979 but significantly increased during 1980–2019. The 120‐year trend pattern of the wind decay period has been found to be correlated with the Atlantic Multidecadal Oscillation. Meanwhile, we show that the storm's distance of movement is not changing simultaneously with the decay period due to the variance of storm translation speed. The spatial variation of the wind decay is also confirmed. While the majority of the historical Gulf landfall hurricanes decayed below tropical storm strength, landfalling hurricanes over Florida in particular, tend to cross the peninsula retaining wind speeds greater than 34‐kt.